Age, skills and labour market outcomes in Finland - Pareliussen, Jon (OECD Publishing, 2016)
Macro-simulations benchmarking employment in Finland to the Nordic average show that closing the large gaps in labour participation vis-à-vis the other Nordics across genders and age groups would boost employment significantly. Regressions on micro-data from the OECD Survey of Adult Skills (PIAAC) show how skills, education and other socio-economic background variables explain some of the observed differences in labour market outcomes across age and gender. Low employment in the oldest Finnish cohorts is partly a result of a large skills gap vis-à-vis younger generations. This Working Paper relates to the 2016 OECD Economic Survey of Finland (www.oecd.org/eco/surveys/economic-survey-finland.htm)
Keywords: Economics; Finland